Assessing the Ability to Use eHealth Resources Among Older Adults: Cross-Sectional Survey Study - Bernard Aoun; Jon O Ebbert; Priya Ramar; Daniel L Roellinger; Lindsey M Philpot (JMIR Formative Research)
Abstract BackgroundIncreasing reliance on digital health resources can create disparities among older patients. Understanding health-related, mobility, and socioeconomic factors associated with the use of eHealth technologies is important for addressing inequitable access to health care. ObjectiveWe sought to assess digital health literacy among patients aged ≥65 years and identify factors associated with their ability to access, understand, and use digital health resources. MethodsWe developed a survey instrument grounded in the Technology Acceptance Model and conducted a cross-sectional, mixed-mode survey of patients aged ≥65 years from an integrated, multispecialty medical center. Digital health literacy was measured using the eHeals health literacy scale, and responses were analyzed across self-rated health, self-reported mobility, and socioeconomic deprivation assessed with the Area Deprivation Index (ADI). Counts (n) and frequencies (%) are reported across response groups, and analyses for differences are performed using the χ2 ResultsAnalyses included 878 responses (response rate=878/2847; 30.8%). There was a significant difference in the distribution of race between responders and nonresponders (PPPP ConclusionsOur findings highlight the need for targeted interventions to improve engagement with eHealth among patients aged ≥65 years, who are impacted by poor health, limited mobility, and socioeconomic deprivation. Enhancing digital health literacy can help bridge the gap in access to digital health resources and improve overall health outcomes for this population.